Orbitofrontal response to drug‐related stimuli after heroin administration. (11th April 2014) - Walter, Marc; Denier, Niklaus; Gerber, Hana; Schmid, Otto; Lanz, Christian; Brenneisen, Rudolf; Riecher‐Rössler, Anita; Wiesbeck, Gerhard A.; Scheffler, Klaus; Seifritz, Erich; McGuire, Philip; Fusar‐Poli, Paolo; et al.
Abstract The compulsion to seek and use heroin is frequently driven by stress and craving during drug‐cue exposure. Although previous neuroimaging studies have indicated that craving is mediated by increased prefrontal cortex activity, it remains unknown how heroin administration modulates the prefrontal cortex response. This study examines the acute effects of heroin on brain function in heroin‐maintained patients. Using a crossover, double‐blind, placebo‐controlled design, 27 heroin‐maintained patients performed functional magnetic resonance imaging 20 minutes after the administration of heroin or placebo (saline) while drug‐related and neutral stimuli were presented. Images were processed and analysed with statistical parametric mapping. Plasma concentrations of heroin and its main metabolites were assessed using high‐performance liquid chromatography. Region of interest analyses showed a drug‐related cue‐associated blood‐oxygen‐level‐dependent activation in the orbitofrontal cortex (OFC) in heroin‐dependent patients during both treatment conditions (heroin and placebo). This activation of the OFC was significantly higher after heroin than after placebo administration. These findings may indicate the importance of OFC activity for impulse control and decision‐making after regular heroin administration and may emphasize the benefit of the heroin‐assisted treatment in heroin dependence.